Efektivitas Penggunaan Instagram melalui Dua Tahap Analisis pada Zanana dan Oifyoo - Anastasya Maharani; Irfan Ardiansah; Totok Pujianto (Universitas Katolik Parahyangan, 2019)
The using of social media for marketing in products and services industry is currently trending, both in small and big enterprises. Zanana and Oifyoo are among the SMEs that already used Instagram to market their products. The purpose of this research is to find the effectiveness of using social media (Instagram) as online marketing on Zanana and Oifyoo. Zanana has a specified marketing team to manage their Instagram account> Meanwhile, Oifyoo's Instagram account is managed by the owner directly. The analysis of Instagram using effectiveness is much needed for increasing marketing, sales, or branding purposes. This research is done with a few steps including data reduction, data serving, conclusion, and verification. There are two data used in this research, primary and secondary data. The primary data is accumulated using in-depth interviews and the secondary data is retrieved on both SMEs Instagram accounts. This research used media and network analyses to analyze the data. The research shows that Zanana is more excelled at the effectiveness of using Instagram in both media and network analyses than Oifyoo. Keywords: effectiveness, Instagram, media analysis, network analysis